The effects of trade, aid, and investment on China's image in developing countries - Vera Z. Eichenauer; Andreas Fuchs; Lutz Brückner (University of Heidelberg, Department of Economics, 2018)
One goal of China's Go Out policy is to create goodwill in countries around the world. At the same time, China's growing economic engagement has provoked much criticism. This paper is the first to study whether these activities change the attitudes of individuals in developing countries towards China at both the national and subnational level. Using repeated cross-sectional survey data from the Latinobarómetro, we analyze whether and how growing amounts of exports, foreign aid, and foreign direct investment from China to Latin America affect opinions on China within 18 Latin American countries over the 2002-2013 period. We run instrumental-variables regressions by exploiting exogenous variation in the supply of Chinese exports, aid, and investment proxied by China's market penetration of developing countries outside Latin America. In contrast to the widespread criticism, we do not find evidence that China's growing economic activities in the respective countries deteriorate average attitudes towards China - neither at the national nor the provincial level. However, our results show that the young, educated, and economically privileged population develops more positive views of China. We interpret this as evidence that China's economic engagement creates winners and losers.
urn:nbn:de:bsz:16-heidok-242095
Keywords: F14; F15; F21; F35; F61; O54; P33; 330; public opinion; exports; development assistance; foreign direct investment; China; Latin America; anti-Sinicism; soft power